The faunal and geochemical approaches in the calcareous microfossils and their applications to the palaeoceanography and palaeoclimatology - Bergue, Cristianini Trescastro; Coimbra, João Carlos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
Micropalaeontology is an important ally to the palaeoceanography and palaeoclimatology contributing to the study of factors such as sedimentation rates, sea level and hydrological changes (e.g. circulation, temperature, productivity and salinity). This revision article aims to present the main applications of three important groups of calcareous microfossils: nannofossils, foraminifers and ostracodes. Species composition and geochemical approaches on those groups both in Cretaceous and Cenozoic are discussed based on studies published in the last years, referring whenever it possible to examples of studies developed in Brazil.